The Strategy of Business Performance Development for UPPKS in Facing the Demographic Bonus Era - Wyati Saddewisasi; Surjawati; Aprih Santoso (Yayasan Ahmar Cendekia Indonesia, 2022)
The basic problems faced by UPPKS in Semarang are as follows (Jateng Pos, 2019): 1) Many group businesses do not develop and